2022
DOI: 10.1108/ijmf-09-2021-0435
|View full text |Cite
|
Sign up to set email alerts
|

The best-fitting model(s) of equal risk contribution: evidence from environmental-friendly portfolio

Abstract: PurposeThis research aims to select the best-fitting model(s) of equal risk contribution portfolios (ERC). ERC is a robust estimation in the absence of reasonable expectations about future returns.Design/methodology/approachThe portfolio consists of five environmental-friendly exchange-traded funds (ETFs). It applies equal risk optimization, beneficial when the assets are firmly linked, such as the ETFs. This paper operationalizes 20 covariance models in portfolio construction, and a portfolio with classic cov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 77 publications
0
1
0
Order By: Relevance
“…Finally, the third trend explicitly explores our study's object: green bonds and portfolio analysis. Here, we find the research developed by [10,11,14,[60][61][62][63][64]]. Firstly, for example, refs.…”
Section: Branches and Leavesmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, the third trend explicitly explores our study's object: green bonds and portfolio analysis. Here, we find the research developed by [10,11,14,[60][61][62][63][64]]. Firstly, for example, refs.…”
Section: Branches and Leavesmentioning
confidence: 99%
“…Finally, refs. [10,62] contribute to the evolution of portfolio theory by examining portfolio construction techniques, risk dynamics, dependence structures, and diversification benefits within specific asset classes.…”
Section: Branches and Leavesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the seventh paper, Nugroho intends to select the best-fitting model(s) of equal risk contribution (ERC) portfolios, which is a robust estimation approach in the absence of reasonable expectations about future returns. Nugroho (2022) examined a portfolio consisting of five environmentally friendly exchange-traded funds and operationalized 20 covariance models in portfolio construction, and a portfolio with classic covariance is the benchmark to beat. After using statistical inferences of the model confidence set to find the best fitting model, the author found that ERC can benefit from copula-based covariance and that the outbreak of COVID-19 hugely impacts the portfolio drawdown.…”
Section: Introductionmentioning
confidence: 99%